Reliability and validity of the online Pittsburgh sleep quality index in college students from low-income regions - Augusto César Ferreira De Moraes; Augusto César Ferreira De Moraes; Augusto César Ferreira De Moraes; Lorrane Cristine Conceição da Silva; Lorrane Cristine Conceição da Silva; Barbara Saldanha Lima; Kliver Antonio Marin; Ethan T. Hunt; Marcus Vinicius Nascimento-Ferreira; Marcus Vinicius Nascimento-Ferreira (Frontiers Media S.A., 2024)
ObjectivesWe aimed to test the reliability and structural validity (also called dimensionality) of the online Pittsburgh Sleep Quality Index among college students from low-income regions.MethodsWe assessed 195 Brazilian college students from a low-income region (Gini index of 0.56), of whom 117 were reassessed to evaluate the reliability. We collected all data in a self-reported online twice, 2-week apart. We evaluated reliability and structural validity.ResultsAll questionnaire components showed reliability, correlation coefficient ≥0.49. In the structural validity, the confirmatory analysis showed better global model adjustment for the one-factor (RMSEA = 0.019; SRMR = 0.041; CFI = 0.992; TLI = 0.986) solution compared with two-factor (RMSEA = 0.099; SRMR = 0.070; CFI = 0.764; TLI = 0.619) and three-factor (RMSEA = 0.108; SRMR = 0.066; CFI = 0.763; TLI = 0.548) solutions, respectively.DiscussionThe online questionnaire presents acceptable reliability and structural validity in Brazilian low-income regions.